Interlocking Inequalities: Digital Stratification Meets Academic Stratification. (August 2018) - Robinson, Laura; Wiborg, Øyvind; Schulz, Jeremy
This article examines the effects of digital inequality in conjunction with curricular tracking on academic achievement. Capitalizing on an original survey administered to seniors (fourth-year secondary school students), our survey data ( N = 972) come from a large American public high school with a predominantly disadvantaged student body. The school's elective tracking system and inadequate digital resources make for an excellent case study of the effects of a differentiated curriculum and digital inequalities on academic achievement. Multilevel random-effects and fixed-effects regression models applied to the survey data reveal the important role played by digital inequalities in shaping academic achievement as measured by GPA. As the models establish, academic achievement is positively correlated with both duration of digital experience and usage intensity regarding academically useful computing activities, even when students' curricular and class placement are taken into account. In contrast, both leisure computing and smartphone usage are negatively correlated with academic achievement as measured by GPA. Also with regard to GPA, findings show that students in the higher curricular tracks benefit more from longer durations of digital experience than do students in lower curricular tracks. These results underscore the importance of focusing attention on the ways in which digital inequalities combine with curricular tracking in shaping academic achievement.